Financial Service Company Fair Valuation by Using the Excess Return Model, Case Study of PT. BPR Fajar Warapastika - Nugok, M. Dye Ralang; Soekarno, Subiakto (Universitas Teknokrat Indonesia, 2023)
In the evolving financial landscape of Indonesia, the consolidation of rural banks has been identified as a potentially significant trend. Given the escalating consolidation trend among rural banks in Indonesia, accurate company valuation has become crucial in enabling strategic decision-making, particularly in potential shareholder exit activities or divestment. The objective is to assess the fair valuation of PT. BPR Fajar Warapastika, a rural bank located in Lampung, by using an Excess Return Model. The Excess Return Model, chosen for its robust evaluation of intrinsic company value, takes into account the cost of equity, expected return on equity, and book value of equity. This comprehensive analysis is augmented by an assessment of significant financial ratios, including Capital Adequacy Ratio, Non-Performing Loan, Return on Asset, Operating Expense to Operating Revenue, Loan to Deposit Ratio, and Cash Ratio. This approach offers a holistic insight into the company's financial health and performance.